Exotic decay channels are not the cause of the neutron lifetime anomaly - Dubbers, Dirk (Physics letters, 2019)
Since long neutron lifetimes measured with a beam of cold neutrons are significantly different from lifetimes measured with ultracold neutrons bottled in a trap. It is often speculated that this “neutron anomaly” is due to an exotic dark neutron decay channel of unknown origin. We show that this explanation of the neutron anomaly can be excluded with a high level of confidence when use is made of our new result for the neutron decay β asymmetry. Furthermore, data from neutron decay now compare well with Ft-data derived from nuclear β decays.
Available online: 15 February 2019
Gesehen am 16.04.2019